Skills to act from a Positive Health approach: in comparison with shared decision-making: a scoping review - Visser, Renske; Veehof, Martine; van Hogen-Koster, Sandra, on behalf of the RENurse Consortium (Frontiers in Public Health, 2025)
IntroductionPositive Health (PH) is a health approach that expands the definition of health, emphasizing social, psychological, and personal perspectives. PH helps healthcare professionals to provide insight into a patient’s perceived health and gives them insight into their health improvement. PH is acknowledged for improving healthcare and quality of life, but the practical implementation of PH and the necessary skills for healthcare professionals remain unexplored. The overall aim of this review is to explore and map the Positive Health skills needed for healthcare professionals in a variety of healthcare settings.MethodsA scoping review was conducted. PubMed, Embase, and CINAHL were searched using the key term “Positive Health” AND “healthcare professionals” AND “skills” including synonyms and related keywords. Initial searches yielded fewer relevant studies than expected. Therefore, a revised strategy incorporated “Shared Decision-Making (SDM)” AND “healthcare professionals” AND “skills” to enhance the search. The methodological quality was assessed. A convergent integrated approach synthesized findings and identified overarching skills. An overview was made to visualize the skills.ResultsAfter screening, 15 studies were included. The five overarching skills are: “applying a holistic approach”, “communicating and active listening”, “managing time effectively”, “encouraging patient participation”, “reflecting and self-reflection”.DiscussionAn overview of PH skills was obtained, where the comparison with SDM led to more foundation and more strategies for PH skills. Increasing PH skills in clinical practice may improve implementation. Further research is needed to explore if PH and SDM are mutually reinforcing.